A EFETIVIDADE DOS DIREITOS FUNDAMENTAIS COMO INSTRUMENTO DE INCLUSÃO PARA A CIDADANIA - Padoin, Fabiana F.; Ramos, Lizelia T.; Mainardi, Fernando A.; Kruger, Felipe O.; Taube, Aline T. (Salão do Conhecimento, 2013)
Resumo